2012
DOI: 10.1073/pnas.1220456110
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ mediates chemokine-dependent recruitment of natural killer cells during viral infection

Abstract: Natural killer (NK) cells provide in vivo control of orthopoxvirus infections in association with their expansion in the draining lymph node (LN), where they are normally very rare. The mechanism of this expansion is unclear. Herein, we determined that NK-cell depletion results in enhanced infection following footpad inoculation of cowpox virus, a natural pathogen of rodents. Following cowpox virus infection in normal mice, NK cells were greatly expanded in the draining LN, were not replicating, and displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 69 publications
(77 reference statements)
9
80
0
Order By: Relevance
“…It therefore indicated that the observed NK-cell chemotaxis in the conditioned medium of the LPS-stimulated mature DCs was partially dependent on the CXCR3 signaling in the IL-2-activated NK cells. Indeed, we detected also high concentration of interferon gamma inducible protein (IP-10) [24,45] in the conditioned medium of the LPS-stimulated mature DCs (Table 1), thus corroborating further with the significance of the CXCR3:IP-10 ( Table 2) axis in the regulation of NK-cell migration in the NK cell-DC crosstalk. …”
Section: Nk-cell Chemotaxis In a Conventional Trans-well Systemsupporting
confidence: 80%
See 1 more Smart Citation
“…It therefore indicated that the observed NK-cell chemotaxis in the conditioned medium of the LPS-stimulated mature DCs was partially dependent on the CXCR3 signaling in the IL-2-activated NK cells. Indeed, we detected also high concentration of interferon gamma inducible protein (IP-10) [24,45] in the conditioned medium of the LPS-stimulated mature DCs (Table 1), thus corroborating further with the significance of the CXCR3:IP-10 ( Table 2) axis in the regulation of NK-cell migration in the NK cell-DC crosstalk. …”
Section: Nk-cell Chemotaxis In a Conventional Trans-well Systemsupporting
confidence: 80%
“…They Correspondence: Dr. Sam K. P. Kung e-mail: Sam.Kung2@med.umanitoba.ca acquire specific chemokine surface receptors during development and maturation [2,[10][11][12][13][14][15]. Chemokine receptors such as CCR7, CCR5, and CXCR3 are involved in the preferential migrations and localization of NK cells into the LNs [8,[16][17][18][19], whereas NK cells reside in blood, liver, and spleen exhibit higher CXCR1 and CX 3 CR1 expression [8,9,[20][21][22][23][24][25]. Nonchemokine family proteins such as chemerin and SIP 5 are also involved in the regulation of NK-cell trafficking [26,27].…”
mentioning
confidence: 99%
“…Genes up regulated in C14R NK cells were associated with the mitochondrion and cell differentiation, while genes involved in protein processing in the endoplasmic reticulum, transcriptional regulators and cellular organization were downregulated (Figure 5D and E). However, genes such as Cxcr3 and Cxcr4 , both of which are essential for infiltration and function of NK cells, 3032 and the transcriptional regulator Nab2 were upregulated in Ly5.1 C14R . We observed that in Ly5.1 C14R mice, the number of NK cells found in the lung were enriched ~2.1 fold indicating that the failure of tumor control was not driven by the inability to migrate to the lung.…”
Section: Resultsmentioning
confidence: 98%
“…For example, NK cells can be recruited to draining LNs by activated dendritic cells (DCs) (Martin-Fontecha et al 2004). During orthopoxvirus infection, NK cells are recruited to the draining LN (Parker et al 2007;Fang et al 2008;Pak-Wittel et al 2013). The recruited NK cells resemble splenic NK cells by phenotypic markers; adoptively transferred splenic NK cells also appear in the draining LN in a pertussis-toxinsensitive manner partially dependent on the chemokine receptor CXCR3 (Pak-Wittel et al 2013).…”
Section: Lymph Node Nk Cellsmentioning
confidence: 99%
“…During orthopoxvirus infection, NK cells are recruited to the draining LN (Parker et al 2007;Fang et al 2008;Pak-Wittel et al 2013). The recruited NK cells resemble splenic NK cells by phenotypic markers; adoptively transferred splenic NK cells also appear in the draining LN in a pertussis-toxinsensitive manner partially dependent on the chemokine receptor CXCR3 (Pak-Wittel et al 2013). Recruitment required IFNg because recruitment did not occur in IFNg receptor -deficient mice or when wild-type (WT) mice were administered anti-IFNg-neutralizing antibody.…”
Section: Lymph Node Nk Cellsmentioning
confidence: 99%